Lanthanide Complexes in Molecular Magnetic Resonance Imaging and Theranostics. (30th May 2017) - Lacerda, Sara; Tóth, Éva
Abstract: Lanthanide complexes have attracted much attention in the biomedical field, and today various imaging applications make use of their versatile magnetic and luminescence properties. In this minireview, we give insight into the mechanistic aspects that allow modulation of the relaxation or chemical exchange saturation transfer (CEST) features, and thus the magnetic resonance imaging (MRI) efficiency of paramagnetic lanthanide chelates in order to create agents that are capable of providing an MRI response as a function of a specific biomarker. We focus on the detection of neurotransmitters, enzymatic activities, and amyloid peptides. We also describe two selected theranostic strategies: 1) a novel approach directed at monitoring drug release from liponanoparticles and 2) molecular or nanoparticle probes for the MRI visualization of photosensitizer delivery in photodynamic therapy. Abstract : With their versatile magnetic and optical properties and rich coordination chemistry, lanthanide complexes offer boundless possibilities to create molecular imaging and theranostic agents. This minireview discusses examples of smart magnetic resonance imaging (MRI) probes with specific responses to neurotransmitters or enzymes, MRI targeting of abundant peptides, luminescence monitoring of nanoparticle integrity, or combining PDT and MRI.